Studying Structural Behavior of Concrete Faced Rockfill Dam Using Finite Element Method - Al-Obaidi, Fayda F. (2005)
Concrete faced rock fill dam has been increasingly popular among dam engineers due to their inherent advantages over other type of dams. The construction of concrete faced rockfill dam has been conducted in full swing in recent years. But still there is some crucial problems needed further investigation. In this study an attempt has been made to investigate various aspects related to the structural analysis of concrete face rockfill dams, this involved, physical modelling, constitutive modelling, effect of concrete slab and simulation of sequence of construction. To model sequential stages of construction of concrete faced rockfill dam the Dead- Birth-Ghost element technique was used. The physical modeling was carried out using finite-infinite elements to represent bedding media, eight and six noded isoparametric elements were used for modeling the dam body and the concrete face respectively. Moreover the interfacial behavior between the concrete face and the body of the dam was modeled using interface element. The constitutive modeling has body of the dam was modeled using interface element. The constitutive modeling has been accounted by employing the hyperbolic nonlinear elastic model. So based on the above physical and material modeling a two dimension linear and nonlinear finite element program with different type of isoparametric elements was written. The verification of the program was well established by analyzing certain bench mark examples. The applicability of the above program has been illustrated by analyzing two concrete faced rockfill dam namely; Kavar dam currently under construction in Iran (53.5 m), and Bakun dam currently under construction in the state of Sarawak Malaysia (205 m). The results indicates that the sequences of construction, reservoir filling and nonlinear material behavior have significant effects on the structural response of the dam in terms of displacement and stresses and need to be considered for accurate prediction of the structural behavior of the dam and focuses on the effect of face slab on the distribution of deformation and stresses developed due to the static loading including gravitation and reservoir loading.